Control of postharvest diseases caused by Penicillium spp. with myrtle leaf phenolic extracts: in vitro and in vivo study on mandarin fruit during storage. (23rd January 2021) - Fadda, Angela; Sarais, Giorgia; Lai, Carla; Sale, Luana; Mulas, Maurizio
Abstract: BACKGROUND: In the postharvest handling of horticultural commodities, plant extracts with fungicidal activity are a valid alternative to synthetic fungicides. The fungicidal activity of myrtle leaf extracts from eight cultivars was studied in vitro against Penicillium digitatum, Penicillium italicum, and Penicillium expansum and on artificially inoculated mandarins with green and blue molds during storage for 12 days at 20 °C and 90% RH. RESULTS: Hydroxybenzoic acids, hydrolysable tannins, and flavonols were identified by high‐performance liquid chromatography (HPLC). Despite sharing the same phenolic profile, extracts of eight myrtle cultivars significantly differed in the concentration of phenolics. Hydrolysable tannins are the principal subclass representing nearly 44.9% of the total polyphenols, whereas myricitrin was the most abundant flavonol in all cultivars. Myrtle extracts strongly inhibited conidial germination of the pathogens tested, although the greatest efficacy was observed against P. digitatum . At a concentration of 20 g L −1, all the extracts completely inhibited fungi growth; only 'Angela', 'Tonina' and 'Grazia' extracts were effective at lower concentrations (15 g L −1 ). On inoculated fruit, myrtle extracts significantly controlled rot development. As a preventive treatment, 'Ilaria' and 'Maria Rita' extracts significantly reduced the rate of fruit with green mold decay lesions. When applied as a curative treatment, all the exacts decreased the incidence of decay. Against P. italicum, all the extracts applied as preventive treatments controlled decay effectively, while as curative treatment some of the extracts were not effective. All the extracts reduced the size of the infected areas. CONCLUSION: The results propose myrtle extracts as a possible natural alternative to synthetic fungicides. © 2021 Society of Chemical Industry